(untitled) (Bangladesh Journal of Agricultural Research, 2023)
Fifty-six hybrids of Tossa jute (Corchorus olitorius L.) were raised at Hajee Mohammad Danesh Science and Technology University, Dinajpur from the parental lines O-9897, O-795, JRO-524, Acc.-2381, Acc.-3423, Acc.-3438, Acc.-3533 and Acc.-3860 and studied. Maximum 24 genotypes were in cluster II followed by 11 in I, 9 in IV, 6 in VI, 4 in V and only 2 in cluster IV and the minimum (2.871) was between the clusters IV and V. Cluster VI produced the highest mean values for all the characters indicated the higher potential. Intracluster distances were lower than inter-cluster distances, suggested less diversity within a cluster. Mahalanobis D2-statistics for genetic divergent classified those 56 genotypes into six clusters. Cluster VI showed the highest intercluster distance (23.565) with cluster I. Therefore, jute breeders may consider the hybrids having desirable trait of cluster I and VI for further improvement of Tossa jute. Bangladesh J. Agril. Res. 46(2): 195-202, June 2021